Peningkatan Keterampilan Menulis Teks Diskusi dengan Menggunakan Media Diorama pada Peserta Didik Kelas IXE SMP Negeri 1 Gabus Kabupaten Grobogan: Array - Khristian Wahyuningtyas (eductum: Jurnal Literasi Pendidikan, 2023)
This study aims to improve discussion text writing skills using diorama media in class IXE students of SMP Negeri 1 Gabus. The research method used is Classroom Action Research (CAR) by taking the subject of class IXE students at SMP Negeri 1 Gabus. This research was conducted in the 2019/2020 school year, starting from January 2020 to March 2020. Writing discussion text skills were measured based on the percentage of achievement scores in writing discussion texts. The research implementation procedure was carried out in two cycles. The implementation of the actions in the second cycle emphasizes the aspects of the improvement that are not optimal in the first cycle. Data collection techniques are in the form of observations, tests, and documentation of learning activities in the form of photos. The criteria for the success of the action are in the form of improving the process and results of students' discussion text writing skills using diorama media. The success of the process can be seen from the increase in enthusiasm and attitudes of students in participating in learning. The success of writing skills is measured based on the achievement score of the discussion text writing aspect of 80. The results of the study obtained that the improvement of discussion text writing skills can be seen based on the students' test results in the pre-action with an average score of 53.94, the first cycle with an average score of 66.25 and in the second cycle the average score was 85.15. An increase in the number of discussion text writing skills scores from pre-action to cycle I of 12.31 and an increase in score from cycle I to cycle II of 18.90. Judging from the qualitative score, the frequency of students' scores in each cycle has increased quite well. So, it can be concluded that the use of diorama media can improve the skills of writing discussion texts for class IXE students of SMP Negeri 1 Gabus.